Clays in complementary and alternative medicine. (November 2014) - Sánchez-Espejo, R.; Aguzzi, C.; Salcedo, I.; Cerezo, P.; Viseras, C.
Abstract : In western countries complementary and alternative medicine is used to sustain the mainstream medical practice (biomedicine). Nowadays, it is used to treat diseases, but also in the prevention, health promotion and health maintenance. Complementary and alternative medicine includes treatments that do not involve use of material substances (mind body treatments), but also other therapies including the use of materials in their treatments. Clays are frequently used as biomaterials with clinical applications in complementary and alternative medicine, as actives and excipients. The uses of clay materials in these medicines are revised, including homeopathy, balneotherapy, natural health substances (i.e. food supplements), as well as other traditional therapeutic systems as Ayurveda and traditional Chinese medicine, with increasing presence in western countries.